Strategi Komunikasi Organisasi dalam Meningkatkan Efektivitas Program Kerja Mahasiswa: Studi Kasus Organisasi Mahasiswa IAI Nasional Laa Roiba Bogor - Bayu Segara Putra Firdenik; Siti Mahmudah Noorhayati (PT Bukuloka Literasi Bangsa, 2026)
Organizational communication plays a strategic role in supporting the successful implementation of student work programs in higher education institutions. Student organizations, as platforms for developing leadership potential and social skills, require effective communication strategies to ensure that all activities are well coordinated and aligned with predetermined goals. This paper aims to describe and analyze organizational communication strategies applied within student organizations at IAI Nasional Laa Roiba Bogor and their implications for the effectiveness of student work programs. The approach emphasizes an in-depth understanding of communication processes occurring during the planning, implementation, and evaluation of work programs. The findings indicate that vertical, horizontal, and informal communication implemented in an open and participatory manner enhances interdepartmental coordination, clarifies task distribution, and encourages active member participation. The use of digital communication media also contributes to faster information dissemination and minimizes communication barriers. Furthermore, dialogical organizational communication strengthens motivation, sense of belonging, and member responsibility toward work program implementation. Therefore, well-planned, adaptive, and inclusive organizational communication strategies are key factors in improving the effectiveness of student work programs and strengthening the performance of student organizations at IAI Nasional Laa Roiba Bogor. Keywords: Organizational Communication Strategies, effectiveness of student programs, internal communications